2012
DOI: 10.1111/j.1365-2702.2012.04203.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching spiritual care – a grounded theory study among undergraduate nursing educators

Abstract: Nursing students need role models who demonstrate spiritual care in the fast-paced hospital environment as well as in other clinical practice settings. To model spirituality as part of nursing care can assist students to overcome their vulnerability and to safeguard ethical issues and promote patient integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 29 publications
2
57
0
2
Order By: Relevance
“…The same has been reported in nursing education [28,29]. Additionally, in a well-founded theory to investigate how nursing educators prepare students to assess and address spirituality, role-modeling and mentoring were also emphasized [45]. Other particular strategies in the teaching of spirituality have been reported, such as caring for patients in different clinical placements, i.e., while on a religious pilgrimage [46].…”
Section: Discussionmentioning
confidence: 95%
“…The same has been reported in nursing education [28,29]. Additionally, in a well-founded theory to investigate how nursing educators prepare students to assess and address spirituality, role-modeling and mentoring were also emphasized [45]. Other particular strategies in the teaching of spirituality have been reported, such as caring for patients in different clinical placements, i.e., while on a religious pilgrimage [46].…”
Section: Discussionmentioning
confidence: 95%
“…A further study by Cone and Giske (2013), explored teachers' understanding of spirituality, and how to prepare undergraduate nursing students to recognise spiritual cues, and learn to provide spiritual care. This grounded theory project with 19 participants, found that 'Journeying with Students through Maturation' resolved their main concern.…”
Section: Spirituality Content In Pre-registration Educational Programmesmentioning
confidence: 99%
“…This involved raising awareness of the essence of spirituality, assisting students to overcome personal barriers, and mentoring students' spiritual care competency. The conclusion was that it is necessary to be explicit, with a continuous input throughout nursing programmes to prepare students to recognise and act on spiritual cues (Cone and Giske, 2013).…”
Section: Spirituality Content In Pre-registration Educational Programmesmentioning
confidence: 99%
“…Education should focus on holistic patient care with attention to spiritual and existential themes throughout the nursing program to help students integrate learning into the clinical practice [54].…”
Section: Areas Essential For Learning Spiritual Carementioning
confidence: 99%